2019
DOI: 10.1177/1932202x19860210
|View full text |Cite
|
Sign up to set email alerts
|

“That’s the Point of Going”: A Qualitative Inquiry Into the Experiences of Black Males at an Early College High School

Abstract: Early college high schools are small schools designed to increase college and career readiness for groups underrepresented in higher education. While some research has focused on student experiences in the early college environment, few have specifically examined the perceptions of Black male students. The purpose of this study was to examine the perceptions of Black males in an early college high school. Using a qualitative case study design, data were collected using focus groups and individual interviews. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…If counselor expectations are negative, deficit based, and anti‐Black, then their interactions with Black male students may be harmful, as their expectations will hinder a trusting student–counselor relationship. Counselors’ perceptions are important to whether Black male students seek out school counselors’ help or benefit when they do meet for counseling (Adams et al., 2020; Brooms, 2021; Bryan & Gallant, 2012). This study indicates that negative counselor expectations may account for why Black male students are less likely to trust counselors (Brooms, 2021; Bryan & Gallant, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If counselor expectations are negative, deficit based, and anti‐Black, then their interactions with Black male students may be harmful, as their expectations will hinder a trusting student–counselor relationship. Counselors’ perceptions are important to whether Black male students seek out school counselors’ help or benefit when they do meet for counseling (Adams et al., 2020; Brooms, 2021; Bryan & Gallant, 2012). This study indicates that negative counselor expectations may account for why Black male students are less likely to trust counselors (Brooms, 2021; Bryan & Gallant, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The factors that were salient to counselors’ characteristics and quality relationship included high expectations, trust, relational caring, and dedications. More specifically, relationships with school counselors were important for Black male students, when there is relational trust and they feel as if the school counselor is investing in them and have high expectations for them (Adams et al., 2020; Brooms, 2021; Bryan & Gallant, 2012). Relatedly, a qualitative study of 215 Black male high school students about their perceptions on school counselors and school counseling services revealed that Black males recognize the importance of school counselors, but 38%−53% perceived school counselors as unfriendly, inaccessible, and untrustworthy (Bryan & Gallant, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a longitudinal interview study of DE students, Karp (2012) found that throughout a semester of DE courses students gained a deeper understanding of the variety of expectations placed on college students. Students frequently describe this experience as a key benefit from DE and gain practical skills like organization and ideas about the importance of being engaged in classes (Adams et al, 2020;J. M. Johnson et al, 2021;Kanny, 2015;Lile et al, 2018;Vásquez-Colina et al, 2022).…”
Section: Social Outcomes De Varies From Other Credit-bearing Transiti...mentioning
confidence: 99%
“…This policy decision then directly impacts equitable opportunities for students as states with greater financial incentives for DE participation have smaller racial enrollment gaps (Xu et al, 2021). The funding structure of DE is also important as the financial savings of DE are often among the key reasons why students participate when states or districts pay for DE (Adams et al, 2020;Hornbeck et al, 2023; T. E. Johnson & Brophy, 2006;Starkey, 2020). Yet, costs to institutions are one of the top barriers for DE for both colleges and K-12 schools (Belfield et al, 2023;Kilgore & Wagner, 2017) and can create tension between these institutions (Hornbeck et al, 2023;Howley et al, 2013).…”
Section: Access To Dual Enrollmentmentioning
confidence: 99%
See 1 more Smart Citation